Scale‐dependent effects of conspecific negative density dependence and immigration on biodiversity maintenance. Issue 7 (16th April 2020) - May, Felix; Wiegand, Thorsten; Huth, Andreas; Chase, Jonathan M.
Abstract : Conspecific negative density dependence (CNDD) has been highlighted as a main driver of biodiversity maintenance. However, while there is general consensus on the scale‐dependent and interacting nature of ecological processes, there is limited knowledge about the relative importance of CNDD across spatial scales and on its interaction with other processes, such as dispersal and immigration. While many studies have detected CNDD at local scales, it remains unknown whether its effects on biodiversity maintenance scale‐up to landscapes and regions. Here, we use a generic dynamic and spatially‐explicit simulation model to assess the interacting relative effects of local‐scale CNDD and immigration from a metacommunity for biodiversity maintenance across spatial scales. For this purpose, we systematically varied immigration rates, the average strength and the variation of CNDD among species. We found that CNDD only determined species richness in strongly isolated communities with little or no interspecific variation in CNDD. In closed communities, plausible interspecific variation in CNDD led to a strong reduction in species richness. In open communities, realistic levels of immigration overwhelmed the effects of CNDD on diversity maintenance. From these results, we suggest that local CNDD is unlikely to be a main driver of biodiversity in real communities, especially at larger spatial scales. This study provides a first step towards improved integration of local‐scale coexistence theory with large‐scale metacommunity theory and highlights the importance of considering the interacting and scale‐dependent nature of ecological processes.